Time, frequency, and time‐varying Granger‐causality measures in neuroscience. (15th March 2018) - Cekic, Sezen; Grandjean, Didier; Renaud, Olivier
Abstract : This article proposes a systematic methodological review and an objective criticism of existing methods enabling the derivation of time, frequency, and time‐varying Granger‐causality statistics in neuroscience. The capacity to describe the causal links between signals recorded at different brain locations during a neuroscience experiment is indeed of primary interest for neuroscientists, who often have very precise prior hypotheses about the relationships between recorded brain signals. The increasing interest and the huge number of publications related to this topic calls for this systematic review, which describes the very complex methodological aspects underlying the derivation of these statistics. In this article, we first present a general framework that allows us to review and compare Granger‐causality statistics in the time domain, and the link with transfer entropy. Then, the spectral and the time‐varying extensions are exposed and discussed together with their estimation and distributional properties. Although not the focus of this article, partial and conditional Granger causality, dynamical causal modelling, directed transfer function, directed coherence, partial directed coherence, and their variant are also mentioned.